LAW HARMONIZATION ON HEIR RESPONSIBILITY OF PERSONAL GUARANTOR IN BANKRUPT COMPANY - Lenny Nadriana (Jurnal Dinamika Hukum, 2018)
The heirs who are taken as bankruptcy debtor is based on the court's decision Article 1826 BW, as a result, the inheritance and their personal property shall be carried out as public confiscation under Article 1 paragraph 1 of the Bankruptcy Law. This research employs normative juridical research method. Public confiscation includes all of debtor’s wealth that will be bankruptcy boedel. Whereas Article 209 the Bankruptcy and PKPU Law stipulates the separation of inheritance boedel and personal property of the heirs. This disharmony among Article 1826 BW, Article 1100 BW, Article 209 Law of Bankruptcy and PKPU (debt postponement petition) require harmony through revision. The revision through bankruptcy law and PKPU comprehends liability limitation of heir as bankruptcy debtor to pay the debts as well as the separation of heir personal property and the inheritance.Keywords: law harmonization, heirs, personal guarantee.